Europe in the media : a comparison of reporting, representation, and rhetoric in national media systems in Europe - Kevin, Deirdre (European Institute for the Media series., 2003)
Europe in the Media draws together the results of several research projects that examined media coverage of European political and cultural affairs and media representations of Europe.